2015
DOI: 10.1007/s11284-015-1327-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wood thrush (Hylocichla mustelina) movement patterns to explain the spatial structure of American ginseng (Panax quinquefolius) populations

Abstract: American ginseng (Panax quinquefolius) is America's premier wild‐harvested, medicinal plant that inhabits the forest understory of eastern deciduous forests. Recent research revealed that birds, particularly wood thrushes (Hylocichla mustelina), disperse ginseng seeds by regurgitating viable seeds 15–37 min after consuming the berries. We carried out two studies to examine the potential effect of thrushes on spatial dispersion patterns of ginseng. First, to analyze how far wood thrushes could disperse seeds, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Additionally, although fertility of surviving individuals increased directly following the ice storm, many of the berries that were produced desiccated prior to dispersal (J.L. Chandler and J.B. McGraw, personal observation), limiting both seed viability and the potential for long‐distance dispersal via frugivorous birds (Hruska, Souther & McGraw ; Elza, Slover & McGraw ). Further, the above‐ground portion of the plants at the WKY populations began senescing earlier in the fall than plants in many other routinely censused populations that were not included in this study (J.L.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although fertility of surviving individuals increased directly following the ice storm, many of the berries that were produced desiccated prior to dispersal (J.L. Chandler and J.B. McGraw, personal observation), limiting both seed viability and the potential for long‐distance dispersal via frugivorous birds (Hruska, Souther & McGraw ; Elza, Slover & McGraw ). Further, the above‐ground portion of the plants at the WKY populations began senescing earlier in the fall than plants in many other routinely censused populations that were not included in this study (J.L.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that natural dispersal may have been difficult owing to geographical and climatic isolation and that some mediator was needed for migration. It has previously been suggested that birds or small mammals might have carried Panax species into North America [76][77][78] . Furthermore, during the Early Pleistocene, the steppe mammoth (Mammuthus trogontherii), a trunked mammal, was estimated to have migrated from Eurasia to North America around 1.3-1.5 Ma 79 , coinciding with the split between P. ginseng and P. quinquefolius in this study (Figs.…”
Section: Evolution Of the Aralia-panax Group And Two Independent Migr...mentioning
confidence: 99%
“…4) [72][73][74] , and the second stage was migration of P. quinquefolius (node 106 in Fig. 4), which occurred during recurrent glaciations and was likely mediated by animals, including birds and small mammals 33,35,[76][77][78] , as well as trunked mammals.…”
Section: Evolution Of the Aralia-panax Group And Two Independent Migr...mentioning
confidence: 99%
“…While population growth rate was stimulated by the ice storm, leaves of plants that remained were noticeably thickened and showed signs of photooxidation (Chandler and McGraw, personal observations). Additionally, although fertility of surviving individuals increased directly following the ice storm, many of the berries that were produced desiccated prior to dispersal (Chandler and McGraw, personal observation), limiting both seed viability and the potential for long-distance dispersal via frugivorous birds Elza, Slover & McGraw 2015). Further, the aboveground portion of the plants at the WKY populations began senescing earlier in the fall than plants in many other routinely censused populations that were not included in this study (Chandler and McGraw, personal observation), a pattern also observed in Panax ginseng grown under high irradiance (Parmenter and Littlejohn 2000).…”
Section: Discussionmentioning
confidence: 99%